Physiological Response of Two Amaranth Varieties (Amaranthus tricolor L.) to Urea Applications - Sari, Fevi Catur Wulan; Purwanto, Edi; Rahayu, Muji; Sakya, Amalia Tetrani (PLANTA TROPIKA, 2024)
Amaranth, a highly nutritious leaf vegetable, requires adequate nutrients, especially nitrogen fertilizers, to grow well and produce an optimal yield. Urea is commonly used to promote the growth of amaranth plants. This study examined the physiological responses of two varieties of amaranth to the application of urea fertilizer. This study examined the physiological responses of two varieties of amaranth to the application of urea fertilizer. This investigation was conducted in July - August 2023 in Sukosari Village, Jumantono, Karanganyar. The study utilized a completely randomized design (CRD) with two treatment variables. The first variable consisted of a variety of amaranth, including green (B1) and red (B2) varieties. The second variable in the study was the dosages of urea, including 0, 50, 100, 150, 200, 250, and 300 kg.ha-1. The study observed no correlation between various varieties of amaranth and the dose of urea applied in terms of plant growth and physiological activities. There was no discernible impact on the growth or physiological activity of both varieties of amaranth when urea fertilizer was applied. Both varieties of amaranth showed similar physiological responses to urea fertilization. However, the effect of adding urea fertilizer was to enhance the vegetative growth of amaranth plants.